#1**0 **

We need to get a common denominator. Let's multiply the first fraction by 3/3 .

\(\frac{\sqrt5}{10}+\frac{\sqrt2}{6}+2 \\~\\ =\,\frac{\sqrt5}{10}\cdot\frac33+\frac{\sqrt2}{6}+2 \\~\\ =\,\frac{3\sqrt5}{30}+\frac{\sqrt2}{6}+2\)

Now let's multiply the second fraction by 5/5 .

\(=\,\frac{3\sqrt5}{30}+\frac{5\sqrt2}{30}+2\)

And multiply the 2 by 30/30 .

\(=\,\frac{3\sqrt5}{30}+\frac{5\sqrt2}{30}+\frac{60}{30}\)

Now we can add the fractions together.

\(=\,\frac{3\sqrt5+5\sqrt2+60}{30}\)

.hectictar Nov 4, 2017